Law and cognitive linguistics : a prototype theory approach to legal categorisation - Zeifert, Mateusz (Abingdon, Oxon [UK] ; New York, NY : Routledge, 2024)
"This book advances the prototype theory of categorisation within a legal context. The work adopts a multidisciplinary approach and draws on insights from cognitive psychology, cognitive linguistics and analytic philosophy to discuss semantic problems present in law. Designed as a bridge between cognitive linguistics and legal theory, it argues that categorisation is a crucial cognitive operation for the application of law and that theories of categorisation are relevant to legal theory. It makes the case that the prototype approach is better suited than more formal approaches usually utilised in jurisprudence to explaining many familiar linguistic problems found in law, such as vagueness, polysemy, the flexibility of meaning, the generality of language, context-dependence of meaning, linguistic indeterminacy, and so on. The book focuses on problems of semantic analysis in law, both in concrete cases, that is, particular cases before courts, and, at the theoretical level, on methods of statutory interpretation. It will be a valuable resource for academics and researchers working in the areas of Law and Language, Legal Theory, Legal Philosophy and Legal Linguistics"--
The prototype theory -- Categoristation in law -- Case studies -- Three problems of legal theory.
Keywords: Semantics (Law); Law -- Language; Law -- Philosophy; Cognitive grammar; Cognitive psychology; LAW / Jurisprudence; LANGUAGE ARTS & DISCIPLINES / Semantics; LAW / Legal Writing